The influence of recovery management on arm muscle strength in the basketball team of SMA negeri 8 Malang - Gusti Rafi Pangestu; Prisca Widiawati; Muhammad Putra Ramadhan (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study aims to determine the influence of recovery management on the arm muscle strength of the basketball team of SMA Negeri 8 Malang. Using an experimental "one-group pretest-posttest design," the study involved 24 athletes, consisting of 12 male and 12 female participants. The measurements of muscle strength were conducted using an expanding dynamometer before and after the implementation of recovery management techniques, including Cold Water Immersion (CWI), foam rolling, elevation, and Proprioceptive Neuromuscular Facilitation (PNF). The results showed a significant improvement in the pull muscle strength of female athletes, with an average pretest score of 18.66 and a posttest score of 20.58, yielding p = 0.029. However, no significant improvement was found in their push muscle strength, as the pretest score was 16.66 and the posttest score was 19.33, yielding p = 0.056. For male athletes, no significant difference was found in muscle strength for either pull (p = 0.183) or push (p = 0.232). These findings indicate that recovery management was more effective for improving the pull muscle strength of female athletes, potentially due to physiological, hormonal, and muscle adaptation differences. The study concludes that recovery management effectively enhances arm muscle strength, particularly in the pull muscles of female athletes, but is less effective for other conditions, as shown by the pretest and posttest analysis of male athletes, where no significant improvement in arm muscle strength was observed.